#### numeriprimi

##### New member

- Joined
- Sep 30, 2017

- Messages
- 1

**[FONT="]Hello everyone.[/FONT]**

I have to prove this equations:

a) Σ (from k=1 to n) (k

b) Σ (from k=1 to n) 2

I know how to solve it with mathematical induction. However, I can't. I have to find a different way. But I dont't see how. Please, could you tell me how to do it?

Thank you.

I have to prove this equations:

a) Σ (from k=1 to n) (k

^{2}+1)*k!=n*(n+1)!b) Σ (from k=1 to n) 2

^{n-k}*k*(k+1)!=(n+2)!-2^{n+1}I know how to solve it with mathematical induction. However, I can't. I have to find a different way. But I dont't see how. Please, could you tell me how to do it?

Thank you.